Concept Water in the Metaphorical Field of Nazar Fedorak's Works (Linguostylistic Studies, 2019)
The article analyzes the concept of water in the poetic works of Nazar Fedorak. The study has revealed and described the most efficient productive verbalizators, delineated semantic spheres that form the meanings of the concept, and documented unique author’s personal elements in the content development of the concept. The case study of the poetic works elucidated a distinct predominance of the negative emotional and social background in the image of water, and its strong correlation with danger, degradation, and death. Both traditional symbolic elements of the image content and the author’s individual elements are used in the image creation.The concept of water is highly productive in the imagery system used by Nazar Fedorak. The frequency of this image usage in the poet's idiolect, revealed in the collections issued with an interval of 17 years, underpins this conclusion. The semantic potential of the image of water is obviously quite powerful, but when compared to the ethnolect imagery system, it is somewhat narrowed. The analysis of the concept in the works of Nazar Fedorak has identified some peculiarities in the reproduction of reality based on the metaphoric image of water. Most images of water are marked with a wailful emotional background. Most often, the poet refers to the concept, correlating it with troubles, anxiety, danger. The concept of water often conveys the meaning of transience of time, decline, death, destruction, and oblivion. Modeling the figurative meaning of water-element, the author emphasizes its primordiality, eternity, variability, and destructive nature. These images are traditional associations with water power, including autumn and winter landscapes. In addition, the poet links the meteorological realizations of the poetic image of water with the concepts of pairing and love, which are among symbolic meanings of water in the folklore. It is worth mentioning that due to the productivity of the anthropo-zoomorphic metaphors, primarily related to the phenomena of nature, the concept of water acquires the meanings of a creature, human, and animal. The study sheds light on the author’s rethinking of water as a victory (a hint of the text “The Tale of Igor's Campaign”) and water (snow) as lyrical hero (individual author’s images).Further research is suggested to determine the concept of water in the idiolects of contemporary authors representing the postmodern trend in the Ukrainian literature.
Keywords: concept; context; connotation; individual style; linguistic picture of the world